Knowledge, attitude, and perception of prescribers about antimicrobial stewardship in a tertiary care hospital - Patil, Jayesh Pralhad; Baig, Mirza Shiraz; Kulkarni , Vishal Ashok (International Journal of Research in Medical Sciences, 2023)
Background: Irrational antimicrobial use has contributed to amplification and spread of antimicrobial resistance (AMR). Antimicrobial stewardship by healthcare personnel can reduce AMR. The World Health Organization (WHO) has established a worldwide action plan to address AMR, including free online availability of open WHO courses. So, our study sought to ascertain knowledge, attitude, and practice (KAP) of healthcare personnel concerning AMS at tertiary care hospital. Methods: Study was conducted as a KAP survey among practitioners (faculty, senior and junior residents) from several departments of Government Medical College, Aurangabad, Maharashtra. A validated questionnaire with 30 questions was prepared and distributed to 100 participants. The data collected in MS excel was analyzed with descriptive statistics and results expressed as mean and standard deviation, frequencies, and percentages. Results: Response rate was 16.7% (n=100). Knowledge on AMS was observed among doctors’ with >80% near correct responses in each question. Insignificant knowledge gap was found comparing between faculty members, senior residents, and junior residents (p>0.005) in the knowledge, attitude and practice of antimicrobial use. All participants felt that ASP is a requirement of hospital, and it minimizes healthcare expenditures and negative impacts of inappropriate AM prescribing. Conclusions: All HCPs have a knowledge gap on ASP, although there is no significant difference in knowledge, attitude, and practice of antimicrobial use between faculty members and senior and junior residents. This demonstrates importance of faculty members taking lead in incorporating more practice and education into ASP.